Determinan Kepuasan, Kepercayaan dan Loyalitas Pelanggan UKM Sasirangan Melalui Media Sosial Instagram (Studi Pada Pelanggan yang merupakan Followers/Pengikut Kasasiur_Banjar ) - Rizki Adhani; RR Yulianti Prihatiningrum (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
This study aims to analyze the influence of User Interface Quality (X1), Information Quality (X2), Privacy Perception (X3) and Price (X4) on Satisfaction (Y1), analyze the influence of User Interface Quality (X1), Information Quality (X2), Privacy Perception (X3) and Satisfaction (Y1) on Trust (Y2) and analyze the influence of Satisfaction (Y1) and Trust (Y2) on Customer Loyalty (Y3).This research is a quantitative study using a survey approach. This research method uses a questionnaire with 150 respondents who are Instagram followers with kasasiur_banjar accounts. In this study using the Non Probability Sampling technique by purposive sampling. Measurement of variables using a Likert scale technique with a scale of weights from 1 to 5. To determine the effect of the studied variables Structural Equation Modeling (SEM) analysis tools are used.The results of the study concluded that User Interface quality has a significant positive effect on customer satisfaction. User Interface quality has a significant positive effect on customer trust. Information quality has a significant positive effect on customer satisfaction. The quality of information t has a significant positive effect on customer trust. Privacy perception has a significant positive effect on customer satisfaction. Privacy perception has a significant positive effect on customer trust. Price has a significant positive effect on customer satisfaction. Customer satisfaction has a significant positive effect on trust. Customer satisfaction has a significant positive effect on customer loyalty. Customer trust has a significant positive effect on customer loyalty.